The adolescent religious identity development in the transition period: do parents still matter? - Prawitasari, Galuh (Konselor, 2019)
Adolescence often known as a transition period from childhood to adulthood. In this phase, adolescents may experience many changes in their identity toward multiple life domains, including religious domain. There have been extensive studies on religious identity in late adolescence, yet only few have discussed the role of significant persons to develop religious identity. This study aimed to investigate the role of parent-adolescent interactional styles to religious identity status in late adolescence. There were 134 undergraduate students of Universitas Negeri Yogyakarta participated in this study. Data were collected using the Religious Identity Status Scale and Parenting Style Scale and analyzed through descriptive statistic, Pearson's correlation, chip-square, and Contingency Coefficient test. Descriptive analysis showed that all participants have been enabling parent-adolescent interactional style, and 22% participants have achievement religious identity status while 78% others were in searching moratorium status. Contingency Coefficient analysis indicated an adequate strong relationship between parent-adolescent interactional style and adolescent religious identity status.